Guidelines for Complementary Feeding of Infants in the Asia Pacific Region: APACPH Public Health Nutrition Group. (May 2020) - Binns, Colin; Lee, Mi Kyung; Yun Low, Wah; Baker, Philip; Bulgiba, Awang; Dahlui, Maznah; Thuy Duong, Doan Thi; Guldan, Georgia; Hairi, Noran; Hokama, Tomiko; Kagawa, Masaharu; Karunathilake, Indika; et al.
Good nutrition in the first "1000 days, " including breastfeeding and appropriate complementary foods, prepares for a healthy childhood and adult life, also contributes to the prevention of the double burden of malnutrition. Exclusive breastfeeding provides all required nutrients until an infant is around 6 months of age when complementary foods are needed. A literature review was undertaken of complementary foods in the Asia Pacific region. The foods being used at present are often of low nutrient density may provide insufficient amounts of some critical nutrients, and generally the variety is limited. Guidelines for complementary feeding are provided to assist in education and in public health planning.